Increasing Knowledge of Climate Processes in the Context of Sustainable Development (Journal of Educational Sciences, 2019)
Climate change of the Earth under the influence of anthropogenic factor is an actual problem of all mankind. In order to prevent irreversible processes in nature, it is necessary to adhere to the highest humanism, as the main achievement of man. The humanistic idea in society – the concept of sustainable development-is considered as a solution to the problem. In the article we have tried to reveal the problem of increasing climate literacy of students as a direction established by the concept of sustainable development. This problem requires knowledge in climatology. Climate literacy is a problematic issue for a number of reasons. These include some inhibiting factors of the educational process, there is no full content, and as a consequence of the uncertainty of the teachers themselves in their competence in this area. For most, climate change is a controversial issue. The doctrine of climate is not an exact science which is physics, chemistry, on the contrary there is scholasticism, as in biology, geology. Among other equally important factors mentioned in the concept, it is important to develop the pedagogical factor in solving the problem of global climate change. Since the integral content of knowledge determines its implementation in practice through the methods of pedagogy.Key words: global climate change, sustainable development concept, climate literacy, pedagogical factor, project thinking, noosphere paradigm.